Review: Mining, Genealogy of Disaster. Extractivism in America as the origin of Modernity (Terr@ Plural, 2022)
In a civilizing context in which environmental crimes such as Mariana and Brumadinho multiply, in Minas Gerais, especially in the periphery of capitalism, Horacio Machado Aráoz presents his book  Mineração, genealogy of disaster: extractivism in America as the origin of modernity, detailing the historical development of a series of environmental violations and depredations that have occurred on the American continent since colonization.
Keywords: Mining; Territory; Environmental Geography; Politic Ecology